2023
DOI: 10.1007/s11356-023-26268-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of pesticides in bee bread collected from honey bee colonies in an agricultural environment in Switzerland

Abstract: Pesticide contamination of bee products is a widespread phenomenon. Due to its composition, bee bread is affected by both lipophilic and hydrophilic substances. As proof of concept of a monitoring campaign and to better understand the extent of contamination, we developed an analytical method based on a modified QuEChERS extraction, with subsequent separation by liquid chromatography and detection by mass spectrometry. This allowed for the quantitation of 51 agricultural- or beekeeping-associated pesticides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Nowadays, the agriculture intensification linked with higher pesticide use means that pollinators are chronically exposed to an "agrochemical cocktail" during the season (Goulson et al 2015). Therefore, monitoring of pesticide residues, including both the lipophilic and hydrophilic active substances, in bee bread can provide us with valuable information on the use of pesticides in the environment around the colony (Schaad et al 2023) as well as on the exposure level within the colony. Nevertheless, the botanical origin of collected pollen plays an important role in the level of contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the agriculture intensification linked with higher pesticide use means that pollinators are chronically exposed to an "agrochemical cocktail" during the season (Goulson et al 2015). Therefore, monitoring of pesticide residues, including both the lipophilic and hydrophilic active substances, in bee bread can provide us with valuable information on the use of pesticides in the environment around the colony (Schaad et al 2023) as well as on the exposure level within the colony. Nevertheless, the botanical origin of collected pollen plays an important role in the level of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the botanical origin of collected pollen plays an important role in the level of contamination. Some authors observed different seasonal residue contamination profile in bee bread or pollen pellets, which mostly correlated with the flowering periods of main agricultural plants (Friedle et al 2021;Schaad et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of chemical contaminant effects on pollinators involved agricultural chemicals (mainly pesticides, fungicides, and herbicides) or pesticides used for honeybee colony hygiene (Schaad et al, 2023). Studies with industrial chemicals (e.g., polychlorinated biphenyls, polycyclic aromatic hydrocarbons, volatile organic compounds) were not Iovanna et al (2017).…”
Section: Ecotoxicology and Ecologymentioning
confidence: 99%
“…Overall, the three bee species did not show extreme variance in their responses to the chemicals despite differences in life histories. Schaad et al (2023) found 26 pesticides, seven fungicides, and two herbicides in bee bread from honeybee colonies in an agricultural matrix in Switzerland. These studies involved oral exposure; no studies were found on cuticular and/or epithelial exposure, for example, in ground‐nesting bees whose larvae reside in contact with soil or with cell membranes excreted by the mother: this remains an unknown exposure pathway.…”
Section: Effect Of Contaminants On Pollinators and Associated Ecosyst...mentioning
confidence: 99%
“…Other findings reported BB as a powerful biomarker/biomonitor, according to Schaad et al [ 38 ], who quantified pesticides in BB samples collected from honeybees in an agricultural environment in Switzerland. The study results provided a significant basis for monitoring pesticide contamination [ 39 ].…”
Section: Introductionmentioning
confidence: 99%